Synthesis and optimization studies of fructose palmitate - Azalina Mohamed Nasir (School of Bioproses Engineering, 2010)
Fructose palmitate (sugar ester) is a relatively new class of nonionic surfactants. Their excellent biodegradability and low toxicity surfactant as well as effectiveness at extreme temperature, pH salinity show their increasing important in numerous areas of applications. In the present work, sugar ester production was developed by anovel and effective enzymatic methods which can reduce the advantages of conventional chemical process. Direct unprotected sugar and non activated fatty acid were used as astarting material. Combination of supersaturated sugar solution under anhydrous condition and stepwise addition of molecular sieve as water absorbent agent during the reaction were found to be suitable a suitable method in increasing the reaction rate nad fatty acid conversion. In this methods influences of severals parameters were investigated as ascreening to the optimization process.Result from screening were used to optimized and analized fructose palmitate (sugar ester) esterification using a response surface methodology (RSM) based on central composite (CCD). The reusabiliy of the immobilized enzyme was shown good coversion, were greater than 88% of fatty acid conversion after 10th reaction cycles without additional treatment of the immobilized enzymed.